2021
DOI: 10.1038/s41467-021-22801-0
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell profiling of tumor heterogeneity and the microenvironment in advanced non-small cell lung cancer

Abstract: Lung cancer is a highly heterogeneous disease. Cancer cells and cells within the tumor microenvironment together determine disease progression, as well as response to or escape from treatment. To map the cell type-specific transcriptome landscape of cancer cells and their tumor microenvironment in advanced non-small cell lung cancer (NSCLC), we analyze 42 tissue biopsy samples from stage III/IV NSCLC patients by single cell RNA sequencing and present the large scale, single cell resolution profiles of advanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
339
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 409 publications
(413 citation statements)
references
References 38 publications
16
339
3
Order By: Relevance
“…Our results also indicated that two eRNAs are negatively correlated with increased expression of tumor stromal cells (p-value < 0.05) (Figure 2). Stromal cells promote tumor growth by releasing cytokines and growth factors, and the receptors for these ligands are commonly found in cancer cells [29,30]. Advanced-stage tumors often undergo a multitude of interactions with tumor stromal cells and immune cells.…”
Section: Clinical Significance Of Smoking Modulated Ernas On Lusc Pathogenesis and Tumor Developmentmentioning
confidence: 99%
“…Our results also indicated that two eRNAs are negatively correlated with increased expression of tumor stromal cells (p-value < 0.05) (Figure 2). Stromal cells promote tumor growth by releasing cytokines and growth factors, and the receptors for these ligands are commonly found in cancer cells [29,30]. Advanced-stage tumors often undergo a multitude of interactions with tumor stromal cells and immune cells.…”
Section: Clinical Significance Of Smoking Modulated Ernas On Lusc Pathogenesis and Tumor Developmentmentioning
confidence: 99%
“…As the most originating sites of the different lung cancer types were correlated with the areas of distinct epithelial cells and their progenitor cells, even LR-MSCs could hypothetically lead to de-differentiation of lung stem cells, thereby initiating lung cancer; or at least differentiate into (divers) non-tumorigenic stromal cells that ultimately define the histological type of NSCLC [ 12 , 16 , 33 ]. Conformingly, MSC-related marker expressions (e.g., CD90, CD44, CD105, CD73 as well as LR-MSC specific HOX transcription factors) were associated with low pathologic stage in NSCLC and/or accounted for a reduced overall survival of respective patients [ 47 , 48 , 49 , 50 ].…”
Section: The Tumor-promoting Action Of Lung Cancer-associated Mscsmentioning
confidence: 99%
“…Accordingly, high expression levels of ACTA2 (commonly known as alpha-smooth muscle actin or Ī±-SMA), a frequently used marker for myofibroblasts/ CAFs were further associated with poor survival periods in NSCLC [ 66 , 67 ]. Thus, lung CAFs contribute to the malignant signature for advanced stage lung cancer [ 12 ].…”
Section: Lr-mscs As Source Of Activated Fibroblastsmentioning
confidence: 99%
See 2 more Smart Citations